Analisis Pengaruh Ekspor, Impor, Nilai Tukar, dan Inflasi terhadap Cadangan Devisa Indonesia Tahun 1996-2020 - Dinda AB Permana; Sitti Retno Faridatussalam (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
This study aims to analyze the effect of imports, exports, inflation, and exchange rates with Indonesia's foreign exchange reserves simultaneously and partially with a time limit of 1996-2020. This study utilizes secondary data, namely time series data with a period of 25 years. Linear regression is an analytical method used in this study with the Partial Adjustment Model (PAM) approach. The results of this study indicate that there is a positive and significant influence that exists between exports and foreign exchange reserves and there is no significant effect between the research variables.